Control of Neurospora crassa morphology by cyclic adenosine 3', 5'-monophosphate and dibutyryl cyclic adenosine 3', 5'-monophosphate. - Terenzi, H F (1976)
The role of cyclic adenosine 3', 5'-monophosphate (cyclic AMP) in the control of the Neurospora asexual life cycle was studied. Endogenous cyclic AMP levels were 10 to 20 times higher in strains having the wild-type cr-1 allele than in those carrying the mutated allele. In a wild-type strain these levels remained constant throughtout the entire growth period in shaken liquid cultures, except during a short period at the beginning of the stationary growth phase. In this period a marked increase in the cyclic nucleotide level was observed. The culture of cr-1 mutant strains in the presence of cyclic AMP or its dibutyryl derivative restores some morphological properties characteristic of wild-type strains. Specifically these cyclic nucleotides stimulated the rate of mycelial elongation, as well as the differentiation of aerial hyphae.